Audit committee activity and internal control quality in Egypt: Does external auditor's size matter?. Issue 3 (7th March 2016) - Khlif, Hichem; Samaha, Khaled
Abstract : Purpose: – The purpose of this paper is to examine the association between audit committee activity, external auditor's size and internal control quality (ICQ) in the Egyptian setting. It also explores how external auditor's size moderates the relationship between audit committee activity and ICQ. Design/methodology/approach: – To obtain relevant information about ICQ in Egypt, the authors conducted a survey among external auditors using an internal control checklist. Findings: – Results show that audit committee activity has a significant positive effect on ICQ. In addition, Big 4 auditors contribute significantly to the improvement of the ICQ in the Egyptian setting. Finally, the association between audit committee activity and ICQ is more pronounced when an organisation is audited by a Big 4 audit firm. Originality/value: – The results this paper demonstrate that Big 4 auditors play a governance role in weak legal environment as exists in Egypt by strengthening the effectiveness of audit committee meetings. The findings also have policy implications for Egyptian standard-setters and other emerging economies characterised by an under-developed and poorly regulated audit market, with respect to the development of internal auditing standards.